Formation and Application of Core–Shell of FePt-Au Magnetic–Plasmonic Nanoparticles - Wei, Da-Hua; Lin, Tei-Kai; Liang, Yuan-Chang; Chang, Huang-Wei (Frontiers in Chemistry, 2021)
Monodispersed FePt core and FePt-Au core-shell nanoparticles (NPs) have been chemically synthesized in liquid solution and with controllable surface-functional properties. The NP size was increased from 2.5 nm for the FePt to 6.5 nm for the FePt-Au, which could be tuned by the initial concentration of gold acetate coated onto FePt seeding NPs via a seed-mediated formation of self-assembled core-shell nanostructures. The analyses of selective electron diffraction pattern (SAED) and x-ray diffraction (XRD) confirmed that both FePt core and Au shell belong to the face centered cubic (fcc) structure. FePt-Au NPs have a surface plasmon resonance (SPR) peak at 528 nm in the visible optical band region, indicating the red-shift compared with the typical theoretical value 520 nm of pure Au NPs. The surface modification and ligand exchange of FePt-Au was using mercaptoacetic acid (thiol) as a phase transfer reagent that turned the NPs hydrophilic due to functional carboxyl groups bond on the surface of presented multi-functional magnetic-plasmonic NPs. The water-dispersible FePt-based NPs conjugated with biomolecules could reach the different biocompatibility requirements and also provide enough heating response that acted as a potential agent for magnetic fluid hyperthermia in biomedical engineering research fields.